Food Safety Knowledge, Attitudes, Practices, and Associated Factors Among Adult Consumers in Bangladesh: Findings From a Nationwide Cross‐Sectional Survey - Nitai Roy; Mohammad Aktarujjaman; Aysha Siddiky; Kakali Mollick; Raphyel Rosby; Bryan T. Rogers; Ekhtear Hossain; Firoj Al Mamun; Mohammed A. Mamun (Health Science Reports)
ABSTRACT Aim This study aimed to evaluate the food safety knowledge, attitudes, and practices (KAP) of Bangladeshi consumers and investigate their associations with various demographic factors. Methods This national cross‐sectional study utilized a face‐to‐face survey using a structured questionnaire to recruit 1400 adult consumers between September 2022 and November 2022. Multiple linear regression analysis was employed to determine the factors associated with the food safety KAP. Results The current findings revealed that consumers had moderate knowledge (overall correct response rate of 65.3% with a mean score of 13.06 ± 2.88 on a scale of 0 to 20), excellent attitudes (overall correct response rate for food safety knowledge was 81.8% with a mean score of 14.72 ± 2.72 on a scale of 0 to 18), and relatively poor practices (overall correct response rate was 51.7% with a mean score of 35.17 ± 11.2 on a scale of 0 to 68). Participants who were male, had higher education, were employed, were familiar with the Bangladesh Food Safety Authority, and residing outside the Mymensingh division, demonstrated greater food safety knowledge. However, participants from Barisal, Rangpur, and Dhaka, who were less educated, had fewer children, and only occasionally cooked, had negative attitudes about food safety. Additionally, individuals from all administrative divisions except Mymensingh and Chittagong, who were employed, had fewer children, had experienced food poisoning, and had inadequate food safety practices. Conclusion These findings suggest that the Bangladeshi government should intensify efforts to enhance consumer awareness regarding food safety.